Decisões arquitetônicas x potência instalada para o sistema de condicionamento de ar: estudo de caso Palácio Gustavo Capanema - Sandra Ricardo Botrel e Silva (2014)
The design of a mechanical air conditioning system is of fundamental importance when considering the energy efficiency of the buildings and the reduction in energy consumption, once this system is responsible for a large share of energy consumption in artificially conditioned buildings. Several decisions made during the development of the architectural design have direct implication on the thermal loads. However, this impactsare not avaliated in a integrated way during the project design. This study presents a comparative evaluation of the results of the calculation of the thermal loads of the Gustavo Capanema Palace, located in Rio de Janeiro, based on the utilization of passive solar protections usedin the original design, as well as, variations of the glass shading coefficient. The simulations were carried out using the software TRACE 700. Based on the simulations,the calculation of the thermal load was been carried out, comparative analyses were prepared the results of the thermal load, the initial investment, the electrical consumption and the cost of the energy. It was verified that the variation of the thermal load showed different values from the variation of the initial investment, electric power and consumption, due to of the modulation of the capacity of the commercialequipment. The thermal load ranged from +12,5% if they were not used the passive measures in the building and 9,3% if the existing windows were replaced with more efficient glasses. The initial investment of the HVAC system ranged from +16,7 % and 5,0% the annual energy consumption ranged between +31% and13,1% and the cost of energy between +21,3% and - 6,5%. The operation of theair conditioning system in a hybrid mode with the natural ventilation presents a reduction in the energy consumpti on of -11% in an automatic operation and 9,8%, in a manual operation.